IMPLEMENTASI METODE CIPP PADA EVALUASI PROGRAM PENGENDALIAN VEKTOR DI RUMAH SAKIT UNTUK MENURUNKAN RISIKO PENULARAN PENYAKIT (Studi di Rumah sakit Royal Surabaya Tahun 2020) - Kartika Diyah Rachmawati; Rusmiati .; Khambali . (Poltekkes Kemenkes Surabaya, 2022)
Vector control is part of efforts to control vector-borne diseases directly or indirectly which aims to reduce the presence of vectors by implementing preventive measures so that disease transmission does not occur. The vector-borne and zoonotic disease control programs carried out include reduction, elimination, and eradication. The number of vectors at the Royal Surabaya Hospital in 2018 contained 52.5% mosquito vectors, 27.5% cockroach vectors, 57.5% ants, and 30% rats. Density increased in 2019, namely mosquito vectors as much as 87.9%, cockroach vectors 30.3%, ants 57.6%, and mice 60.6%. However, it did not experience a significant decrease in 2020 with the number of mosquito vectors as much as 84.6%, cockroach vectors 15.4%, ants 46.2%, and rats 38.5%. The purpose of this study was to evaluate the vector control program using the CIPP method (Context, Input, Process and Product).This research is a descriptive study with an exploratory approach. The sample in this study were 32 heads of the room. Data collection was obtained by conducting interviews using questionnaires and observations at the Royal Surabaya Hospital. The data that has been collected is analyzed descriptively.The result of this research is that the CIPP method can be used to evaluate vector and pest control programs. Context, input, and process evaluations got good categories, while in product evaluation there were still cockroaches, flies, mice, and cats.From this research, it is recommended to close all access to vectors and nuisance animals, to maintain cleanliness, especially in waste management and sewerage, to coordinate with the head of the room, partners and all employees to participate in reducing the presence of vectors.